THE CHALLENGES TO GROW THE NUMBER OF WOMEN AS IT PROFESSIONALS - Cavalier, Maira Rosa; Malagolli, Guilherme Augusto (Revista Interface Tecnológica, 2022)
To talk about women in the Information Technology career, all the social aspects that impact this reality must be taken into account. Women played a very important role in the development of the technological universe. However, currently, the courses related to the Information Technology area are composed mostly by men. In this context, the objective of this article is to analyze how the Information Technology area is seen by the female public today and to suggest actions to increase the presence of women in this area of ​​professional activity. For this, a theoretical research was carried out in order to understand the causes of the low presence of women in the IT market and, later, an empirical research with interviews with several professionals and students in order to find out how is the perception of people connected to the IT market. area on the professional performance of women. After analyzing the information collected, it was possible to notice how social factors influenced the professional choices of the female audience.
Keywords: Women; Technology; Stereotype; Representativeness; Social development